La Migration Terminologique Interdisciplinaire dans le Langage Politique Contemporain - Angela GRĂDINARU; Svetlana CEBOTARI (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
The interdisciplinary terminological migration in contemporary political language refers to the dynamic process of linguistic exchange and adaptation across various disciplines within the political realm. This phenomenon reflects the interconnectedness of diverse fields such as sociology, economics, and international relations, where terminology evolves and transcends traditional disciplinary boundaries. The migration underscores the fluidity of language in addressing complex political issues, fostering a shared lexicon that facilitates communication among experts from different backgrounds. This interdisciplinary approach enhances the precision and inclusivity of political discourse, enabling a more comprehensive understanding of contemporary challenges. It also reflects the evolving nature of political thought, as terms from one discipline find resonance and applicability in others, contributing to a richer and more nuanced vocabulary for discussing global issues. In essence, the migration of terminology across disciplines in contemporary political language promotes collaboration, knowledge integration, and a holistic approach to addressing the multifaceted aspects of the modern political landscape.